EFFECT OF NON-SPHERICITY OF GRAVITATIONAL FIELD OF THE ASTEROID ON THE ITS SATELLITES ORBITS EVOLUTION - Troianskyi, V. V. (Одеські астрономічні публікації, 2016)
Lately it has become possible to sufficiently precise definition of the physical and geometric characteristics of asteroid systems using radar observations (http://echo.jpl.nasa.gov/~lance/binary.neas.html), which allowed calculating the asymmetry of the massive component of double and multiple asteroids for studying the dynamics of motion of their satellites.